2002
DOI: 10.1073/pnas.092031799
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin recognizes misfolded HLA-A2 heavy chains

Abstract: Our studies investigated functional interactions between calreticulin, an endoplasmic reticulum chaperone, and major histocompatibility complex (MHC) class I molecules. Using in vitro thermal aggregation assays, we established that calreticulin can inhibit heat-induced aggregation of soluble, peptide-deficient HLA-A2 purified from supernatants of insect cells. The presence of HLA-A2-specific peptides also inhibits heat-induced aggregation. Inhibition of heat-induced aggregation of peptide-deficient HLA-A2 by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
4
27
1
Order By: Relevance
“…However, these experiments must be interpreted with caution because we cannot rule out that deglycosylation destabilizes class I molecules in a fashion that cannot be reversed by CRT. Moreover, we confirmed that CRT inhibits class I aggregation, both in a direct and indirect fashion (26). CRT directly inhibited precipitation of refolded empty A2SC molecules at 45°C.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, these experiments must be interpreted with caution because we cannot rule out that deglycosylation destabilizes class I molecules in a fashion that cannot be reversed by CRT. Moreover, we confirmed that CRT inhibits class I aggregation, both in a direct and indirect fashion (26). CRT directly inhibited precipitation of refolded empty A2SC molecules at 45°C.…”
Section: Discussionsupporting
confidence: 64%
“…Wearsch et al (11) showed that monoglucosylation of soluble HLA-B8 is both necessary and sufficient to induce class I/CRT interaction but did not study the effect of CRT on peptide assembly with class I (11). The latter issue was investigated by Mancino et al (26) who found that CRT prevented HLA-A2 aggregation at 45-50°C, whereas it had no effect in a peptide exchange assay at physiological temperature.…”
mentioning
confidence: 98%
“…3), coupled with exposure of hydrophobic residues (Fig. 7) at temperatures approaching the T Trans values is likely responsible for the occurrence of calreticulin oligomerization upon heating and cooling (40,41). As such, the findings presented here provide further structural evidence for the notion that the cellular requirements for calreticulin may extend beyond its classical lectin-based functions.…”
Section: Discussionsupporting
confidence: 49%
“…The interaction with calnexin can persist in the presence of castanospermine or in glucosidase-deficient cells for some, but not all, murine and human class I alleles (31,48). In addition, calreticulin can suppress the aggregation at 45-50°C of insect cell-expressed HLA-A2, which is glycosylated but with an unknown and likely processed structure (49). In that study, however, no interaction was observed at physiological temperatures.…”
Section: Fig 6 Binding Of Calreticulin To Glycosylated Mhc Class I mentioning
confidence: 64%
“…In that study, however, no interaction was observed at physiological temperatures. To date, aggregation inhibition assays are the only in vitro techniques successfully used to demonstrate the interaction of calnexin or calreticulin with substrates that are either non-glycosylated or glycosylated with the incorrect structure (37,47,49). The published assays were performed at 45°C, which has been shown to be the T m for the thermal denaturation of calreticulin (50).…”
Section: Fig 6 Binding Of Calreticulin To Glycosylated Mhc Class I mentioning
confidence: 99%